The importance of enhancing, maintaining and saving face in smartphone repurchase intentions of Chinese early adopters: An exploratory study. Issue 3 (7th August 2017) - Filieri, Raffaele; Chen, Wenshin; Lal Dey, Bidit
Abstract : Purpose: China is the world's largest consumer market for smartphones. Early adopters are highly influential in consumers' decisions of new technologies. Therefore, understanding Chinese early adopters' decision making in the smartphone market is of crucial importance to smartphone companies. There is a dearth of in-depth studies on the factors affecting consumers' repurchase intention for smartphones. The purpose of this paper is to narrow this knowledge gap by developing a new conceptual framework explaining early adopters' repurchase intention of smartphones. Design/methodology/approach: Using 30 face-to-face interviews with Chinese early adopters of smartphones, the authors built a new theoretical framework to explain the factors that influence their repurchase intention. Findings: Repurchase intention of smartphones is determined by aesthetic and utilitarian product-related factors (design appeal, perceived usefulness), socio-cultural factors (subjective norms, mianzi / face considerations), and brand-related factors (brand popularity, brand's country of origin, perceived brand quality, and brand loyalty). The emerging framework also explores the factors affecting enhancing, maintaining, and saving mianzi / face . Originality/value: In contrast to existing technology-driven models, the study's emerging framework shows how aesthetic, socio-cultural, and brand-related factors can offer new insights in understanding repurchase intention in a rapidly developing market. As these factors are rarely examined in the information technology and/or marketing literatures, potential knowledge contribution can be highly expected.